ANALYSIS OF RACIAL DISCRIMINATION TOWARDS UNCLE TOM IN HARRIET BEECHER STOWE’S UNCLE TOM’S CABIN - RISMA KARTIKA DEWI; MARTHA INDRIANI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2019)
A racial discrimination gives the impact to other people. A racial discrimination happens because white race is more dominant than black race. A white race feels more superior to the black race. The white race is dominated than black race. The Negro lives in poverty, slavery, human trafficking and physically abused. Many of the black people struggle against the condition of poverty, physically abused and many pressure of life.  There is no law for black people’ right which dominated by the white race and the white race people’ action to the black race cannot be stopped. Furthermore, the researcher is interested to the topic of racial discrimination in the novel of Harriet Becheer Stowe’s Uncle Tom Cabin. The researcher analyzes three main problems that are how racial discrimination depicted in the novel, what are the factors of racial discrimination in the novel and what the effects of racial discrimination in the novel are.The thesis uses descriptive qualitative research method. The data is taken from the quotations in the novel and related to the theory and the quotations will become the proofs of the analysis.  The researcher uses theory of race and racism based on Les Back and John Solomos’ book to analyze the data. The result of the research is that the factors of racial discrimination are slavery and human identity. The human identity refers to the identity of race. In addition, the effects of racial discrimination are human trafficking, family separation, physically abused and rebellion. Keywords: racial discrimination, race, black race